Evaluation of respiratory symptoms and lung function disorders of farmers in Yazd Province - Gholam Hossein Halvani; Reza Jafari Nodoushan; Elham Halvani; Vida sadat Anoosheh (Shahid Sadoughi University of Medical Sciences, 2019)
Abstract Introduction: Respiratory disorders are common problems in farmers which have a high mortality rate in Yazd city. The aim of this study was to evaluate and compare respiratory parameters as well as the prevalence of respiratory symptoms in three age groups in farmers and non-farmers. Methods: This case-control study was conducted on 300 farmers and 300 non-farmers in Yazd. Questionnaires including cognitive knowledge and symptoms of respiratory diseases were completed for all participants and lung function tests were also performed. Data were analyzed using T-student, Chi square test or Fisher's exact test. Results: Spirometric results showed a significant reduction in respiratory capacity in the farmer group compared to non-farmer. In all three age groups, the prevalence of respiratory symptoms in farmers were higher than non-farmer groups and as the age increased, the prevalence of symptoms also increased. In the age group over 55, the risk of cough, phlegm, dyspnea and wheezing were 17,10/ 78,3/58 and 6/61 times more than non-farmers respectively which were statistically significant at 95% confidence interval P value < (0.05). Among the symptoms of respiratory, cough had the highest and shortness of breath had the lowest prevalence. Discussion and conclusion: Regarding the prevention of high prevalence of respiratory disorders in farmers, the mechanization of agricultural practices, the promotion of health awareness of farmers by health professionals, appropriate implementation of training programs by the health department and assistance of Jihad-e-Agriculture are necessary